Endoscopic Ultrasound Findings in Patients Diagnosed with Exocrine Pancreatic Insufficiency by Low Fecal Elastase-1 - Mazen Shobassy; Nedaa Husainat; Abdalaziz Tabash; Kalpesh Patel; Hashem B. El-Serag; Mohamed O. Othman (Gastroenterology Research and Practice)
Background and Aims. Fecal elastase-1 (FE-1) as a screening test for exocrine pancreatic insufficiency (EPI) is gaining popularity in clinical practice. The role of imaging in patients with FE-1-related suspicion of EPI remains unclear. The aim of this study was to characterize endoscopic ultrasound (EUS) findings for patients with low FE-1. Methods. A retrospective cross-sectional study was performed in 40 patients who had low FE-1 and underwent EUS to evaluate the pancreas. We obtained data on demographic and lifestyle factors, EUS findings, and histopathology results. We compared these variables between patients with FE‐1<100 mcg/g vs. 100-200 mcg/g. Results. Most patients (82.5%) established one or more new diagnoses from EUS. Diagnoses included: definitive chronic pancreatitis (n=29, 72.5%), fatty pancreas (n=9, 22.5%), and pancreatic solid mass or cyst (n=9, 22.5%). Half (n=4) of the solid or cystic lesions were neoplastic. All patients with a solid pancreatic mass also had concurrent chronic pancreatitis. There were no significant differences in EUS findings or demographic or lifestyle factors between groups with FE‐1<100 mcg/g vs. 100-200 mcg/g. Conclusion. Chronic pancreatitis is the most common EUS finding in patients with low FE-1 levels. EUS appears helpful in determining the cause of EPI in most patients with low FE-1 and may detect unsuspected pancreatic neoplasia.